Odpowiedzi

Najlepsza Odpowiedź!
2010-02-07T20:35:25+01:00
A) =6x - 24 - 2 = 6x - 26
b)=2x+2-3x+3 = -x+5
c)= -3y+6+4y+8 = y+14
d)=5x-5y-5-4x-8=x-5y-13
e)=6a+2b-2a+2b=4a+4b
f)= 2x-2-2x = 2
g)=x²-x-3x²+3x=-2x²-2x
h)=5a²-15a-3a²+15a=2a²
i)=3x²+xy-xy+y=3x²+y
;))
2010-02-07T20:36:23+01:00
A)
6(x-4)-2= 6x - 24 -2 = 6x - 26

b)
2(x+1)-3(x-1)= 2x + 2 - 3x + 3 = -x + 5

c)
-3(y-2)+4(y+2)= -3y + 6 + 4y + 8 = y + 14

d)
5(x-y-1)-4(x+2)= 5x - 5y - 5 - 4x - 8 = x - 5y - 13

e)
2(3a+b)-2(a-b)= 6a + 2b - 2a + 2b = 4a + 4b

f)
1/2(4x-4)-2x= 2x - 2 - 2x = -2

g)
x(x-1)-3(x do potęgi 2-x)= x² - x -3x² + 3x = -2x² + 2x

h)
5a(a-3)-3a(a-5)= 5a² - 15a - 3a² - 15a = 2a² - 30a

i)
3x(x+1/3y)-2y(1/2x-1/2)= 3x² + xy -xy + y = 3x² + y
2010-02-07T20:41:06+01:00
A) = 6x - 24 - 2 = 6x - 26
b)=2x + 2-3x+3= 5x+5
c)=-3y+6+4y+8=y+14
d)=5x-5y-5-4x-8=x-5y-13
e)=6a+2b-2a+2b=4a+4b
f)=2x-2-2x=-2
g)x do kwadratu - x -3x do potęgi 2 =3x+2do potęgi 2-x
h)5 a do kwadratu - 15a -3 a do kwadratu +15a=2 a do kwadratu
i)3 x do kwadratu + y - yx + y=3 x do kwadratu + 2y - yx

Pozdrawiam ;)